Asymmetric localization of natural antisense RNA of neuropeptide sensorin in Aplysia sensory neurons during aging and activity - Kadakkuzha, Beena M.; Liu, Xin-An; Narvaez, Maria; Kaye, Alexandra; Akhmedov, Komolitdin; Puthanveettil, Sathyanarayanan V. (Frontiers in Genetics, 2014)
Despite the advances in our understanding of transcriptome, regulation and function of its noncoding components continue to be poorly understood. Here we searched for natural antisense transcript for sensorin (NAT-SRN), a neuropeptide expressed in the presynaptic sensory neurons of gill-withdrawal reflex of the marine snail Aplysia californica. Sensorin (SRN) has a key role in learning and long-term memory storage in Aplysia. We have identified NAT-SRN in the central nervous system (CNS) and have confirmed its expression by northern blotting and fluorescent RNA in situ hybridization. Quantitative analysis of NAT-SRN in micro dissected cell bodies and processes of sensory neurons suggest that NAT-SRN is present in the distal neuronal processes along with sense transcripts. Importantly, aging is associated with reduced levels of NAT-SRN in sensory neuron processes. Furthermore, we find that forskolin, an activator of CREB signaling, differentially alters the distribution of SRN and NAT-SRN. These studies reveal novel insights into physiological regulation of natural antisense RNAs.